Factors associated with parental self-medication of antibiotics in health centers of Manila - Bulario, Jamaica S.; Cruz, Ingrid Louise P.; Pilapil, Mycah C. (2017)
This study aimed to identify factors associated with antimicrobial self-medication of mothers for their children aged 18 years old and below. Cross sectional descriptive study was used in which the data were collected through interview using an adapted questionnaire from studies of De Lara et al (2015) and Barber (2016). Purposive sampling was used and a total of 390 mothers were included in the study. The prevalence of parental self- medication using antibiotics was 42.05% and age of mothers was found associated with antimicrobial self-medication to their children (p< 0.029, OR= 1.02). Self-medication using antibiotics was mainly used by mothers for cough (33.54%). Amoxicillin (50.25%) was the preferred antibiotic by mothers, with 54.08% incorrect use. Other antibiotics abused were cephalexin (8.46%), co-amoxiclav (6.15%), erythromycin (4.87%), co- trimoxazole (4.10%), cloxacillin (3.59%), cefuroxime (1.79%) and penicillin (1.79%). Mothers declared that they get antimicrobial information from health centers and other sources (42.68%) followed by old prescriptions (28.66%) and relatives (23.17%). Community pharmacies (85.37%) were the main source of antibiotics followed by health centers (23.17%). It is notable that while there is an increased misuse of antibiotics, however, based on measurement of knowledge, the mothers passed with an average score of 7.63 but have limited understanding of viruses, for only 36.41% of respondents identified that antibiotics should not be used for viral infections. The researchers recommend the strict implementation of the pharmacy regulations regarding the sale of antibiotics and educational interventions about rational use of antibiotics were recommended directed towards mothers.